Concentrated Liquidity in Ethereum Blockchain’s Digital Asset Trading: Insights from Innovative Back-Testing Algorithms - Luo, Kai; Jin, Nanlin; Ma, Jieming (Computational economics, 2025)
Blockchain has started moving to Ethereum, decentralised and open-source. One of the most important application domains of the Ethereum blockchain is decentralised finance (DeFi). It facilitates speed-up trading, in absence of the traditional financial intermediaries, such as brokerages, exchanges, or banks. The three main types of digital asset trading strategies are concentrated liquidity, unbounded liquidity, and grid trading. Concentrated liquidity has recently been designed to increase the liquidity provision that indicates the convertibility of assets. Currently, the performance comparison of these three types of trading remains largely unclear. This research proposes back-testing algorithms to measure their return on investment (ROI). Our research has been conducted on real Ethereum blockchains and has discovered that their ROIs vary and depend on price fluctuation. These findings will shed new insights in the design of future decentralised trading strategies.